The Effect of Comic Strips on Reading Comprehension of The Tenth Grade Students At SMK NU Mambaul Huda Tegalsari In Academic Year 2019/2020 - Fitri Handayani; Wageyono; Nur Hasibin (Prodi Pendidikan Bahasa Inggris, Universitas PGRI Banyuwangi, 2020)
Reading comprehension is a part of English learning in education, the meaning of comprehension is the process of eliciting making meaning thought interaction and involvement with written language. The purpose of this research was to know whether the students taught by using comic strips get better Reading Comprehension of Descriptive text score. The purpose of this research was to know whether the students taught by using comic strips get better Reading Comprehension score of Descriptive text. This research was an experimental research. The type of the research was a pre experimental research. The researcher used one group pretest and posttest design. The respondents of this research were 34 students. Before giving the treatment, the students were given pre-test, and post-test was given after the treatment. The technique of collecting data was a test. The technique of data analysis was T-test formula in order to know the difference between the average of posttest of experimental class and pretest of experimental class. T-test was analyzed and interpreted with the degree of significances 5% with db = 32 and the T-table is 2,021. The results of T-test analysis is 5,27. It means that the T-test ( 5,27 ) is higher than T-table ( 2,021 ) in the significances 5%. From the research finding, it can be concluded that the students taught by using comic strips get better score on reading comprehension of descriptive text. It is suggested for the future researcher to conduct further research on similar area by improving the methodology.